Global, regional, and national burdens of attention deficit hyperactivity disorder in adolescents and young adults aged 10–24 years from 1990 to 2021: A trend analysis - Bo Yuan; Bo Ao; Sajid Ali; Qiong Cai; Yanan Chen; Youliang Huang (PLoS ONE, 2026)
Background Attention Deficit Hyperactivity Disorder (ADHD) is a major neurodevelopmental disorder among adolescents and young adults (AYAs) worldwide. However, there is still insufficient understanding of the burden and trends of this condition. This study aims to assess the trends in the global, regional, and national burden of ADHD among AYAs aged 10–24 years from 1990 to 2021. Methods Based on the Global Burden of Diseases, Injuries, and Risk Factors Study (GBD) 2021, our study reports estimates of the incidence, prevalence, and disability-adjusted life-years (DALYs) of ADHD among AYAs at the global, regional, and national levels, including the corresponding rates and 95% uncertainty intervals (UIs). We also analyzes the trends in the burden of ADHD from 1990 to 2021 from both global and local perspectives, specifically by Estimated Annual Percentage Change (EAPC) and Average Annual Percentage Changes (AAPCs). Additionally, these global trends are further examined according to age, sex, and Socio-Demographic Index (SDI). Results Globally, the incidence of ADHD among AYAs decreased slightly from 12.61 per 100,000 population in 1990 to 11.89 per 100,000 population in 2021, with an EAPC of −0.61% (95% CI −0.79 to −0.43) and AAPCs of −0.17% (95% CI −0.28 to −0.05). The prevalence rate decreased slightly from 2,381.82 per 100,000 population in 1990–2,173.48 per 100,000 population in 2021, with an EAPC of −0.58% (95% CI −0.63 to −0.53) and AAPCs of −0.44% (95% CI −0.47 to −0.42). The rate of DALYs decreased from a 1990 rate of 30.31 per 100,000 population to 26.56 per 100,000 population in 2021, with an EAPC of −0.58% (95% CI −0.63 to −0.52) and AAPCs of −0.44% (95% CI −0.47 to −0.42). In terms of gender, incidence, prevalence and rates of DALYs were higher in males than in females during the same period. In terms of age, the incidence rate originated only from the 10–14 years age group, and only prevalence and DALYs rates were present in the 15–19 years age group and 20–24 years age group and the trend analysis results were correlated with the age group. According to SDI quintiles, incidence, prevalence, and rates of DALYs for ADHD had the highest increases from 1990 to 2021 in areas with a High-middle SDI or High SDI. However, the relationship between incidence, prevalence, and DALYs rates and SDI was nonlinear, and regionally, Australasia had the highest incidence, prevalence, and DALYs rates in 2021, with Western Europe and East Asia having the largest increases in incidence, prevalence, and DALYs rates. In terms of countries, Australia has the highest incidence, prevalence and DALYs rates in 2021, while the UK, Spain and China have the highest rate increases. Conclusions Over the past 30 years, there has been a general downward trend in the incidence and prevalence of ADHD and in the rate of DALYs worldwide. However, phased studies have shown less homogeneous trends in recent years, which may be related to changes in the level of socioeconomic development, diagnostic criteria, and therapeutic approaches. Therefore, it is necessary to continue to promote research on the accuracy and universality of ADHD diagnosis and treatment in the future, with a view to further reducing the global health burden of ADHD.